The Cambridge companion to Gandhi - Brown, Judith M. (Judith Margaret); Parel, Anthony (New York : Cambridge University Press, 2011)
"Even today, six decades after his assassination in January 1948, Mahatma Gandhi is still revered as the father of the Indian nation. His intellectual and moral legacy, encapsulated in works such as Hind Swaraj, as well as the example of his life and politics serve as an inspiration to human rights and peace movements, political activists, and students in classroom discussions throughout the world. This book, comprised of essays by renowned experts in the fields of Indian history and philosophy, traces Gandhi's extraordinary story. The first part of the book, the biography, explores his transformation from a small-town lawyer during his early life in South Africa into a skilled political activist and leader of civil resistance in India. The second part is devoted to Gandhi's key writings and his thinking on a broad range of topics, including religion, conflict, politics, and social relations. The final part reflects on Gandhi's image, how he has been portrayed in literature and film, and on his legacy in India, the West, and beyond"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Political and social views; Statesmen -- India -- Biography